2021
DOI: 10.1021/acsomega.1c00565
|View full text |Cite
|
Sign up to set email alerts
|

Trace-Level Humidity Sensing from Commercial Organic Solvents and Food Products by an AIE/ESIPT-Triggered Piezochromic Luminogen and ppb-Level “OFF–ON–OFF” Sensing of Cu2+: A Combined Experimental and Theoretical Outcome

Abstract: Selective and sensitive moisture sensors have attracted immense attention due to their ability to monitor the humidity content in industrial solvents, food products, etc., for regulating industrial safety management. Herein, a hydroxy naphthaldehyde-based piezochromic luminogen, namely, 1-{[(2-hydroxyphenyl)­imino]­methyl}­naphthalen-2-ol (NAP-1), has been synthesized and its photophysical and molecular sensing properties have been investigated by means of various spectroscopic tools. Owing to the synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 87 publications
1
33
0
Order By: Relevance
“… 38 40 Thus, it can be concluded that the IHB O 1 ···H 1 –N 1 is weakened at the S L state and verified that the reverse proton transfer (RPT) process prefers to proceed at the S 0 state. 41 Most notably, the relative ordering of the IHB intensity at S 0 and S L states for the three investigated compounds is as follows: HQ-k < HQS-k < HQSe-k. Based on the above analysis, it can be inferred that atomic electronegativity can alter the strength of IHB in the S 0 and S L states and thereby affect the proton transfer process of HQ. 41 …”
Section: Results and Discussionmentioning
confidence: 88%
“… 38 40 Thus, it can be concluded that the IHB O 1 ···H 1 –N 1 is weakened at the S L state and verified that the reverse proton transfer (RPT) process prefers to proceed at the S 0 state. 41 Most notably, the relative ordering of the IHB intensity at S 0 and S L states for the three investigated compounds is as follows: HQ-k < HQS-k < HQSe-k. Based on the above analysis, it can be inferred that atomic electronegativity can alter the strength of IHB in the S 0 and S L states and thereby affect the proton transfer process of HQ. 41 …”
Section: Results and Discussionmentioning
confidence: 88%
“…The proposed host–guest interaction mechanism may be explained in terms of different sensing ways that include photoinduced electron transfer (PET), resonance energy transfer (RET), and intermolecular charge transfers (ICT) pathways. In the case of PET, the presence of a low lying vacant π* orbital is necessary to accept an excited state electron from the donor fluorophoric unit. Therefore, PET plays a pivotal role in the quenching efficiency of a particular fluorophore toward a particular analyte. In this context, DFT studies have been performed in order to understand the HOMO–LUMO energy levels of phosphonate MOF (H 8 L-Ti-MOF) and other targeted analytes.…”
Section: Resultsmentioning
confidence: 99%
“…34). All the probes (35)(36)(37)(38) the PET process from the -N centres of the chemosensor skeleton to the vacant orbital of Cu 2+ . Accordingly, the detection limits were found to be 0.12 Â 10 À6 M, 0.10 Â 10 À6 M, 0.097 Â 10 À6 M and 0.098 Â 10 À6 M for 35-38, respectively.…”
Section: Photoinduced Electron Transfer (Pet)-based Sensory Probesmentioning
confidence: 99%
“…Banerjee et al 36 exhibited a fluorogenic sensory probe, 8 , which could selectively detect aqueous Cu 2+ with a detection threshold of 57.2 ppb. In MeOH/H 2 O (60% v/v), 8 remained in the aggregated state, which led to the generation of strong AIE and ESIPT-induced greenish-yellow fluorescence.…”
Section: Chromo-fluorogenic Probes For the Detection Of Cu2+mentioning
confidence: 99%